2014
DOI: 10.1161/circresaha.114.302819
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in Myocardial Matrix and Relevance to Disease

Abstract: T he extracellular matrix (ECM) provides structural support and organization for cardiomyocytes and the vasculature of the heart. Under normal conditions, the ECM scaffold facilitates efficient force transduction for mechanical work, while mediating intercellular communication and metabolic exchange. This follows the unique 3-dimensional disposition of myocyte bundles and fibrillar collagens within the myocardium (Figure 1). With stress, injury, or disease, the ECM undergoes changes that potentiate inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
87
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(89 citation statements)
references
References 144 publications
(164 reference statements)
1
87
0
1
Order By: Relevance
“…48 Results of this study surprisingly indicated that cardiomyocyte-specific overexpression of USP4 dramatically reduced interstitial and perivascular fibrosis. This is plausible when considering that TAK1-(JNK1/2)/P38 serves as an important pathway in the fibrotic response by promoting production of profibrotic factors, such as connective tissue growth factor.…”
Section: Discussionmentioning
confidence: 70%
“…48 Results of this study surprisingly indicated that cardiomyocyte-specific overexpression of USP4 dramatically reduced interstitial and perivascular fibrosis. This is plausible when considering that TAK1-(JNK1/2)/P38 serves as an important pathway in the fibrotic response by promoting production of profibrotic factors, such as connective tissue growth factor.…”
Section: Discussionmentioning
confidence: 70%
“…Color images available online at www .liebertpub.com/tea However, further investigation is warranted regarding, as to which marker is best suited to reflect changes in the setting of MI, because of the complex dynamics of the myocardial ECM responses. 25 Moreover, elastin is one of the major ECM components. In the process of recovering from MI, the necrotic myocardium is replaced by collagen fibers, especially collagen type I and type III, and elasticity is lost in the scarred area.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen synthesis of cardiac myofibroblasts is perceived to be important in the development of cardiac fibrosis (15,16). Therefore, the role of NRG on collagen synthesis was detected via the mRNA levels of CTGF, collagen I and collagen III.…”
Section: Nrg Treatment Inhibits Collagen Synthesis Of Cfsmentioning
confidence: 99%